Hepatitis B serologic patterns in children of HBV carriers or infected mothers - Julfina Bisanto; Imral Chair; Dyah Istikowati (Indonesian Pediatric Society Publishing House, 2016)
Background Vertical transmission is usually the cause of increas- ing carrier rates for hepatitis B infection, especially in highly en- demic areas. Objective To determine the serologic patterns of hepatitis B in children of HBV carrier/infected mothers. Methods This was a cross sectional study on children of HBV carrier/infected mothers. Subjects were recruited consecutively and examined at the Department of Child Health, Cipto Mangunkusumo Hospital during January-July 2003. Children were included if they were generally healthy and their parents gave permission. Chil- dren with chronic illness, previous blood transfusions, or drug abuse were excluded. Results Fifty-nine children of 32 HBV carrier/infected mothers were recruited. HBsAg was positive in 8 children, anti-HBs in 37, and anti-HBc in 4 children. Seventy-three percent of children had been vaccinated against HBV but only 81% had positive anti-HBs. Of eighteen children who received hepatitis B vaccine and HBIg at birth, none was infected. Six out of 25 children who received only hepatitis B vaccine were infected. Conclusion HBsAg, anti-HBs, and anti-HBc were positive in 14%, 36%, and 7% of children of HBV carrier/infected mothers, respec- tively